The Islamic Education Curriculum in the Perspective of Reform: Embracing a Future of Education Rooted in Love - Eva Sunarya; Burniat, Burniat; Ibn Abirul Choir; Dwi Noviani (Bulletin of Pedagogical Research, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping the character and morals of the nation's generation, particularly in facing the challenges of globalization, technological development, and the social ethical crisis. Islamic Religious Education reform is not merely a technical change to the curriculum or learning methods, but rather a paradigm shift in understanding and reinterpreting the essence of religious education. This article aims to examine the new direction of Islamic Religious Education for the future, emphasizing six main pillars of reform: religious moderation, integration of knowledge, a critical and reflective approach, value and character formation, utilization of digital technology, and strengthening collaboration between schools, families, and the community. This study uses a qualitative-descriptive approach through a literature review of academic books, scientific journals, and national education policies. The results indicate that the new direction of Islamic Religious Education must be inclusive, contextual, and adaptive to current developments. A moderate, integrative, and character-based approach is considered crucial in addressing the challenges of radicalism, the dichotomy of knowledge, and moral degradation. Furthermore, the use of big data and artificial intelligence also has the potential to strengthen the personalization of Islamic Religious Education learning more effectively. Future Islamic Religious Education reforms are not only required to produce students who are religiously devout, but also capable of becoming agents of social change who are tolerant, intelligent, and virtuous.